HUKUMAN DAN KEDUDUKAN HAK WARIS BAGI PELAKU EUTHANASIA - Anwar, Wirani Aisiyah (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2018)
Euthanasia is a term used in medical science (medical), activities carried out to speed up the death of the patient who is considered unable to survive anymore. With the sophistication of the modern world now euthasia is considered a necessity, while euthanasia in Islamic law equates its law to murder. Murder is categorized in three forms, namely intentional murder, murder resembles intentional, and murder by mistakes. And euthanasia is divided into two, namely active euthanasia and passive euthanasia. In Islamic law active eythanasia is considered the same as intentional murder so that the perpetrator is subject to a qishash, diat punishment and for heirs or applicants of euthanasia no heir can be said (not receive inheritance from the victim of euthanasia), whereas passive euthanasia is permissible in Islamic law.